Dampak Fatherless terhadap Prestasi Belajar Anak - Siti Fadjryana Fitroh (PG-PAUD Trunojoyo, 2014)
Fatherless can be defined as the absence of a father either physically or psychologically in the child’s life. Fatherless emergence factors may be caused by a divorce, the death of the father, the separation because of problems in the marriage relationship or health problems. Separation between father and son in theform of separation due to the frequency of meetings are rare, although living together but not fully involved in educating children. Fatherless effects experienced by children can be a psychological shock, so that children feel disappointed, frustrated, lazy, not the spirit, which all affect the learning process in schools. Children often feel less motivated than those closest to him, so that the need for achievement, especially in schools is not so considered that decreased.